Large-strain analysis of vertical drain-improved soft deposit consolidation considering smear zone, well resistance, and creep effects. (July 2020) - Nguyen, Ba-Phu; Do, Thanh-Hai; Kim, Yun-Tae
Abstract: The consolidation characteristics of vertical drain (VD)-improved soft deposits depend on the smear zone, well resistance, and creep effects. In this study, we propose a new solution for radial consolidation of VD-improved soft deposits that applies large-strain theory in consideration of smear zone and well resistance effects. A simplified Hypothesis B method is also proposed for calculating the consolidation settlement of VD-improved soft deposits exhibiting creep under different stress states, including overconsolidated and normally consolidated. The proposed solution was verified through application to two case histories of embankments on VD-improved deposits. The numerical analysis showed that the proposed solution provided a satisfactory result that was close to the measured data.